Analisis Isi Kuantitatif Kecenderungan Pesan Politik Standup Comedy Alwi Makkasar Di Konten Somasi Pada Chanel Youtube Deddy Corbuzier - Natasya, Resti; Faris, Faris (Brand Communication, 2024)
The purpose of this research is to determine the tendency of political message content in Alwi Makkasar's stand-up comedy material presented in the "Somasi" content on Deddy Corbuzier's YouTube channel. The research method uses a descriptive quantitative approach. The subjects of this study are the Somasi content uploaded on Deddy Corbuzier's YouTube channel with six scenes as units of analysis. The categories of political messages are propaganda, political advertising, and rhetoric. Reliability testing uses Holsti reliability coefficient and Scott's phi. The data analysis technique uses Content Analysis. The results of the study show the tendency of political messages on sensitive issues about religion and the legitimacy of political figures in the propaganda category, presidential and vice-presidential candidates in the political advertising category, and national identity, nationality, and religion in the rhetoric category